2004
DOI: 10.1128/mcb.24.19.8428-8436.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sox15 Is Required for Skeletal Muscle Regeneration

Abstract: The Sox genes define a family of transcription factors that play a key role in the determination of cell fate during development. The preferential expression of the Sox15 in the myogenic precursor cells led us to suggest that the Sox15 is involved in the specification of myogenic cell lineages or in the regulation of the fusion of myoblasts to form myotubes during the development and regeneration of skeletal muscle. To identify the physiological function of Sox15 in mice, we disrupted the Sox15 by homologous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 38 publications
(43 reference statements)
4
68
2
Order By: Relevance
“…It has been reported that c-Met [89], M-cadherin [90], FoxK [91], Pax7 [15], NCAM [92], syndecan 3 and 4 [93], CD34 [94], caveolin-1 [95], Sox 8 [96], Sox 15 [97], VCAM-1 [98], integrin 7 [99], 1 integrin [100], calcitonin receptor (CTR) [101], lamin A/C [99], emerin [99], Hey1, and Heyl [102] are expressed by quiescent satellite cells, and their expression increases once satellite cells are activated and proliferated [86] (Figure 4). Pax3, the paralog of Pax7, is also expressed in quiescent muscle satellite cells in a subset of muscles.…”
Section: The Phase Of Regeneration Remodeling and Maturationmentioning
confidence: 99%
“…It has been reported that c-Met [89], M-cadherin [90], FoxK [91], Pax7 [15], NCAM [92], syndecan 3 and 4 [93], CD34 [94], caveolin-1 [95], Sox 8 [96], Sox 15 [97], VCAM-1 [98], integrin 7 [99], 1 integrin [100], calcitonin receptor (CTR) [101], lamin A/C [99], emerin [99], Hey1, and Heyl [102] are expressed by quiescent satellite cells, and their expression increases once satellite cells are activated and proliferated [86] (Figure 4). Pax3, the paralog of Pax7, is also expressed in quiescent muscle satellite cells in a subset of muscles.…”
Section: The Phase Of Regeneration Remodeling and Maturationmentioning
confidence: 99%
“…Sox8 and Sox15 are expressed in the satellite cell population in adult skeletal muscle ( Fig. 4; Schmidt et al 2003;Lee et al 2004). Biochemical and overexpression studies suggest that these Sox factors inhibit myogenesis through the transcriptional repression of MyoD family members (Schmidt et al 2003).…”
Section: Nuclear Factorsmentioning
confidence: 99%
“…Thus Sox8 and Sox15 are expressed in muscle satellite cells and are down-regulated during myogenic differentiation (Schmidt et al 2003;Beranger et al 2000). Mice lacking Sox15 are viable but appear to have impaired skeletal muscle regeneration (Lee et al 2004). On the other hand, Sox6 has been shown to play a critical role in the fiber type differentiation of skeletal muscle both in both the mouse and fish.…”
mentioning
confidence: 99%